Quantitvative research methods in corporate finance: Exemplified by stata, python, and R - Mavruk, Taylan (New York Cambridge University Press, 2025)
Focused on empirical methods and their applications to corporate finance, this innovative text equips students with the knowledge to analyse and critically evaluate quantitative research methods in corporate finance, and conduct computer-aided statistical analyses on various types of datasets. Chapters demonstrate the application of basic econometric models in corporate finance (as opposed to derivations or theorems), backed up by relevant research.